Icariin activates far upstream element binding protein 1 to regulate hypoxia-inducible factor-1α and hypoxia-inducible factor-2α signaling and benefits chondrocytes - Pengzhen Wang; Pingping Zhu; Shaoheng Zhang; Wei Yuan; Zhihe Liu (PeerJ, 2023)
Icariin (ICA) is a typical flavonoid glycoside derived from epimedium plants. It has both anabolic and anti-catabolic effects to improve bone mineral density and reduce bone microstructural degradation. However, the effect and underlying mechanism of ICA on the proliferation and metabolism of chondrocyte and synthesis of extracellular matrix are still unclear. This study aimed to investigate the role and regulation of far upstream element binding protein 1 (FUBP1) in chondrocytes treated with ICA to maintain homeostasis and suppress inflammatory responses. In the study, the effect of ICA on chondrocytes with overexpressed or silenced FUBP1 was detected by the MTS and single-cell cloning methods. The expression of hypoxia-inducible factor-1/2α (HIF-1/2α), FUBP1, matrix metalloproteinase (MMP)9, SRY-box transcription factor 9 (SOX9), and type II collagen (Col2α) in ATDC5 cells, a mouse chondrogenic cell line, treated with ICA was evaluated by immunoblotting. Western blotting revealed 1 µM ICA to have the most significant effect on chondrocytes. Alcian blue staining and colony formation assays showed that the promoting effect of ICA was insignificant in FUBP1-knockdown cells (P > 0.05) but significantly enhanced in FUBP1-overexpressed cells (P < 0.05). Western blot results from FUBP1-knockdown cells treated with or without ICA showed no significant difference in the expression of FUBP1, HIF-1/2α, MMP9, SOX9, and Col2α proteins, whereas the same proteins showed increased expression in FUBP1-overexpressed chondrocytes; moreover, HIF-2α and MMP9 expression was significantly inhibited in FUBP1-knockdown chondrocytes (P < 0.05). In conclusion, as a bioactive monomer of traditional Chinese medicine, ICA is beneficial to chondrocytes.